2013
DOI: 10.1080/13557858.2013.771149
|View full text |Cite
|
Sign up to set email alerts
|

Health status and mortality rates of adolescents and young adults in the Brussels-Capital Region: differences according to region of origin and migration history

Abstract: Important differences are observed according to both region of origin and migration history among adolescents and young adults in the BCR. These differences significantly reduce when accounting for education, suggesting that investing in education is a public-health strategy worth considering. Further research in this area may benefit from taking migration history into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 35 publications
(34 reference statements)
1
28
1
Order By: Relevance
“…This healthy-migrant effect is noticeable for FG immigrants of both non-Western and Western origin, and in both men and women, wearing off with the length of stay. Contrary to Razum et al [36] and in line with De Grande et al [5] and Tarnutzer et al [10], this study finds no evidence for the persistence of a healthy-migrant effect into the SG. As indicated by previous research [21], some types of migrants (e.g.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…This healthy-migrant effect is noticeable for FG immigrants of both non-Western and Western origin, and in both men and women, wearing off with the length of stay. Contrary to Razum et al [36] and in line with De Grande et al [5] and Tarnutzer et al [10], this study finds no evidence for the persistence of a healthy-migrant effect into the SG. As indicated by previous research [21], some types of migrants (e.g.…”
Section: Discussioncontrasting
confidence: 56%
“… and in line with De Grande et al . and Tarnutzer et al . , this study finds no evidence for the persistence of a healthy‐migrant effect into the SG.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In proportionate terms, second-generation immigrants represented 6.0% of the total EU population in 2014, up from 5.2% in 2008 (Agafiţei and Ivan 2017). Although research is sparse, second-generation status has been identified in previous studies as an important source of health disparities in EU countries, with important disadvantages in mortality outcomes for certain second-generation subgroups, especially those of non-EU origin (Harding and Balarajan 1996;Razum et al 1998;Tarnutzer, Bopp, and Grp 2012;Scott and Timaeus 2013;De Grande et al 2014;Manhica et al 2015;Vandenheede et al 2015;Wallace 2016;Jervelund et al 2017). Explanations for these mortality disadvantages include lower socioeconomic status, detrimental health behaviors, and chronic stress arising from perceived discrimination (Scott and Timaeus 2013;De Grande et al 2014;Manhica et al 2015;Vandenheede et al 2015;Wallace 2016;Jervelund et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although research is sparse, second-generation status has been identified in previous studies as an important source of health disparities in EU countries, with important disadvantages in mortality outcomes for certain second-generation subgroups, especially those of non-EU origin (Harding and Balarajan 1996;Razum et al 1998;Tarnutzer, Bopp, and Grp 2012;Scott and Timaeus 2013;De Grande et al 2014;Manhica et al 2015;Vandenheede et al 2015;Wallace 2016;Jervelund et al 2017). Explanations for these mortality disadvantages include lower socioeconomic status, detrimental health behaviors, and chronic stress arising from perceived discrimination (Scott and Timaeus 2013;De Grande et al 2014;Manhica et al 2015;Vandenheede et al 2015;Wallace 2016;Jervelund et al 2017). These patterns of excess mortality contrast with the situation of immigrants per se (i.e., the first generation) who tend to experience a mortality advantage despite lower socioeconomic status, a well-known paradox explained in part by migration selection effects (also referred to as the "healthy migrant effect") (Razum et al 1998;Palloni and Morenoff 2001;Bourbeau 2002;Khlat and Darmon 2003;Crimmins et al 2005;Gushulak 2007;Riosmena, Wong, and Palloni 2013;Vang et al 2017).…”
Section: Introductionmentioning
confidence: 99%